2015
DOI: 10.1039/c5ob00372e
|View full text |Cite
|
Sign up to set email alerts
|

Small gold nanoparticles for interfacial Staudinger–Bertozzi ligation

Abstract: Small gold nanoparticles (AuNPs) that possess interfacial methyl-2-(diphenylphosphino)benzoate moieties have been successfully synthesized (Staudinger-AuNPs) and characterized by multi-nuclear MR spectroscopy, transmission electron microscopy (TEM), UV-Vis spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy (XPS). In particular, XPS was remarkably sensitive for characterization of the novel nanomaterial, and in furnishing proof of its interfacial reactivity. These Staudinger-AuNPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…The derivative of the TGA curve showedt hat there are two ligands that decompose at distinctly different temperatures ( Figure S4): al arger component at 265 8Ca nd as mall component at 375 8C. By comparing to the TGA data with that of the MeO-EG 3 -AuNP startingm aterial, the ligand decomposing at 265 8Cw as assigned to MeO-EG 3 -S À , [32,44,45] whereas the ligand at 375 8Cw as assigned to photoDIBO-EG 4 -S À .F rom the combination of 1 HNMR data, deconvolution of the TGA derivative curve, and TEM analysis, and assuming that theseA uNPs are spherical and monodispersed in size, it was possible to calculate an approximate molecular formula of photoDIBO-AuNPs to be Au 800 (MeO-EG 3 -S) 270 (photoDIBO-EG 4 -S) 30 .M ore specifically, these AuNPs contain photoDIBO-EG 4 -S in ac oncentration of 0.136 mmol mg À1 of AuNP.D etails of these calculations are reportedi nt he Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivative of the TGA curve showedt hat there are two ligands that decompose at distinctly different temperatures ( Figure S4): al arger component at 265 8Ca nd as mall component at 375 8C. By comparing to the TGA data with that of the MeO-EG 3 -AuNP startingm aterial, the ligand decomposing at 265 8Cw as assigned to MeO-EG 3 -S À , [32,44,45] whereas the ligand at 375 8Cw as assigned to photoDIBO-EG 4 -S À .F rom the combination of 1 HNMR data, deconvolution of the TGA derivative curve, and TEM analysis, and assuming that theseA uNPs are spherical and monodispersed in size, it was possible to calculate an approximate molecular formula of photoDIBO-AuNPs to be Au 800 (MeO-EG 3 -S) 270 (photoDIBO-EG 4 -S) 30 .M ore specifically, these AuNPs contain photoDIBO-EG 4 -S in ac oncentration of 0.136 mmol mg À1 of AuNP.D etails of these calculations are reportedi nt he Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous work has showedt hat interfacial reactions on AuNPs can be significantly slower than the same reaction carried out in the bulk solution, in which differences dependo nt he mechanistic nature of the interfacial reaction. [45,47] Thus, we were delighted to observen o significant change in the i-SPAAC reactivity at the AuNP interface.…”
Section: Resultsmentioning
confidence: 99%
“…The bioorthogonal nanomaterial template allows for the facile and covalent modification of the nanomaterial’s surface with reactions that are chemoselective, biocompatible, fast, high yielding, and, most importantly, orthogonal to the surface chemistry of the nanomaterial. 4652…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the interfacial chemistry between the two reaction moieties is orthogonal to the surface chemistry of the nanomaterial and leads to the desired (bio)conjugate with no effects on the nanomaterial stability. This approach to conjugation has demonstrated that nanomaterials can potentially be functionalized with any molecular system of interest through easy and reliable chemical reactions (Gobbo et al, ; Gobbo et al, ; Gobbo & Workentin, ; Gobbo et al, ).…”
Section: Introductionmentioning
confidence: 99%